Self-templated chemically stable hollow spherical covalent organic framework - Kandambeth, Sharath; Venkatesh, V.; Shinde, Digambar B.; Kumari, Sushma; Halder, Arjun; Verma, Sandeep; Banerjee, Rahul (Nature communications, 2015)
Covalent organic frameworks are a family of crystalline porous materials with promising applications. Although active research on the design and synthesis of covalent organic frameworks has been ongoing for almost a decade, the mechanisms of formation of covalent organic frameworks crystallites remain poorly understood. Here we report the synthesis of a hollow spherical covalent organic framework with mesoporous walls in a single-step template-free method. A detailed time-dependent study of hollow sphere formation reveals that an inside-out Ostwald ripening process is responsible for the hollow sphere formation. The synthesized covalent organic framework hollow spheres are highly porous (surface area ∼1,500 m 2 g −1 ), crystalline and chemically stable, due to the presence of strong intramolecular hydrogen bonding. These mesoporous hollow sphere covalent organic frameworks are used for a trypsin immobilization study, which shows an uptake of 15.5 μmol g −1 of trypsin. Hollow, spherical nano/microstructures are potentially useful for energy and drug delivery applications. Here, the authors show that these structures can be fabricated from covalent organic frameworks, and exploit their chemical stability and mesoporous structures for enzyme encapsulation.